Biokompatibilnost materialov za izdelavo umetnih kolčnih sklepov - Kocijan, Aleksandra (Vakuumist, 2000)
In this paper the materials i.e. alloys, ceramics and polymers, used in the orthopaedics are presented. The reasons for aseptic loosening are also described.
Keywords: ortopedija; kolki; materiali; ceramic; keramika; polimeri; zlitine; lastnosti